DARI SIRI’ KE SYARI’AT: REKONSTRUKSI PRAKTIK UANG PANAI’ DALAM PERNIKAHAN ADAT BUGIS-MAKASSAR BERBASIS MAQĀṢID AL-SYARĪ’AH - Mutiara; Kurniati; Musyfika Ilyas; Mutiara Mutiara; Kurniati Kurniati (Journal of Innovation Research and Knowledge, 2026)
This study is motivated by the shifting meaning of uang panai’ in bugis-makassar society from a symbol of respect and responsibility into a symbol of social prestige that potentially contradicts the principle of ease in islamic law. This practice has generated various social problems, including high economic burdens, delayed marriages, and family conflicts. This study aims to analyze the practice of uang panai’ from the perspective of islamic law, identify the challenges of its integration with sharia norms, and formulate alignment strategies based on maqāṣid al-sharī‘ah. This research employs a qualitative library-based method using normative-shar‘i, conceptual, and sociology of law approaches. Data were collected from the qur’an, hadith, classical and contemporary fiqh literature, scientific journals, and other relevant references, and were analyzed descriptively, prescriptively, and comparatively. The findings reveal that uang panai’ may be categorized as al-‘urf al-ṣaḥīḥ (valid custom) as long as it is practiced reasonably, based on mutual agreement, and does not impose hardship on the groom. However, contemporary practices indicate a shift toward al-‘urf al-fāsid (invalid custom) due to excessive financial demands that create social harm (mafsadah) and contradict the principle of public benefit (maṣlaḥah) in islamic law. Alignment strategies are carried out through family deliberation, the involvement of customary and religious leaders, adjustment of the amount according to economic capability, and reinterpretation of uang panai’ as a symbol of respect rather than social prestige. This study concludes that reconstructing the practice of uang panai’ based on maqāṣid al-sharī‘ah is essential to maintain a balance between preserving bugis-makassar customs and achieving the objectives of islamic law in creating harmonious, just, and beneficial marriages.